The effect of lignosulfonate chemical stimulator to the metabolites of Euglena sp. - Dwi Hardianti Luthfiana; Khalid Erlangga Karilanata; Khusnul Qonita Maghfiroh; Dedy Kurnianto; Ria Amelia; Tia Erfianti; Ersi Larasati; Renata Adaranyssa Egistha Putri; Eko Agus Suyono (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Euglena sp. contains several metabolites that play a role in various sectors, likely biofuels, food, feed, and pharmaceuticals. Multiple treatments are required to increase the content of Euglena sp. to support its use. In this study, a chemical stimulant in the form of lignosulfonate was added to Euglena sp. in order to increase its natural potency as measured by lipid, carbohydrate, protein, paramylon content, and biomass productivity. lignosulfonate is a macromolecular polyelectrolyte and anionic surfactant which is unique and multifunctional. This lignosulfonate can act as an emulsifier, dispersing agent, binder, and stabilizer of lipids in Euglena sp. cells. This can help improve the physical quality of pellets in Euglena sp. cells. In addition to the lignosulfonate chemical stimulator, it can affect the growth process of Euglena sp. so that it can produce good-quality cells. In addition, it also aims to determine the accumulation of significantly different metabolites. The method used was a Completely Randomized Factorial Design (CRD) with three treatments and three replications. The results obtained indicated that the addition of lignosulfonate was significantly different in the cell and protein density tests. Therefore, the optimal concentration of lignosulfonate can be used as an agent to increase the growth rate and metabolites of Euglena sp. significantly